Echoes of a Warming World: An Ecolinguistics Lens on Salience and Conviction in Global Climate Change Discourse at COP28 - Khan, Abdul Moiz (Pakistan Languages and Humanities Review, 2025)
The current research study delineates the concepts of Conviction and Salience with reference to CoP28, through the selected speeches. In the present era, one of the pressing global issues is climate change, which calls for world leaders to act immediately. So, developing the understanding of the power of language is inevitable in this regard. Therefore, this research study employs a qualitative methodology to unearth these concepts and achieve their objectives. The study examines how speakers emphasize important climate issues, arouse moral and emotional responsibility, and use persuasive language features like modal auxiliaries, personal pronouns, and hopeful framing to encourage international collaboration. The findings show that while emphasis on climate finance, the transition from fossil fuels, and sustainability promotes salience, emotional and moral appeals, inclusive language, and urgency signals strengthen conviction. Hence, to encourage climate action through emotionally and morally compelling messaging, policymakers should take advantage of language's persuasive power.